PENGARUH SID TERHADAP EFEKTIVITAS KINERJA PEMDES - Wijaya, Dian; Rinayuhani, Tri Ratna; Dwi Irmawati, Nila (MAJAPAHIT POLICY, 2023)
Procrastination is the act of delaying starting or completing a task and tends to become a habit, occurring due to a lack of reinforcement, thereby inhibiting performance which can lead to less than optimal performance effectiveness. From the results of the hypothesis test, which states that the value of tcount < ttable, then H0 is accepted and Ha is rejected, with a value of tcount (0.650) > ttable (1.660), using an error level of 5%, with a significance level of 0.88 > 0.05. From these data it can be stated that carrying out procrastination does not reduce the effectiveness of the Pacet District Village Government's performance in administrative services.